2020
DOI: 10.3389/fpls.2020.00321
|View full text |Cite
|
Sign up to set email alerts
|

Coexpression of Sucrose Synthase and the SWEET Transporter, Which Are Associated With Sugar Hydrolysis and Transport, Respectively, Increases the Hexose Content in Vitis vinifera L. Grape Berries

Abstract: The sugar content of grape berries is affected by many factors. To explore the hexose content in different cultivars, the photosynthesis, vegetative, and reproductive biomass, as well as the enzyme activities and expression levels of genes related to sugar metabolism and sugar contents were measured. Samples were collected 70-110 days after anthesis (DAA), from Riesling (RI), Petit Manseng (PM), and Cabernet Sauvignon (CS) berries cultivated in the field. The results indicated that high expression levels of Vv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 77 publications
1
28
0
Order By: Relevance
“…Overexpression of VvSWEET10 in grapevine calli and tomatoes increased the glucose, fructose, and total sugar levels significantly ( Zhang et al, 2019 ). VvSWEET15 was highly expressed in three grape cultivars’ berries and obviously positively correlated with berry hexose content during ripening ( Ren et al, 2020 ). In summary, these findings demonstrated the role of VvSWEETs in sugar accumulation and biotic stress response.…”
Section: Molecular Biology Of Sink Strengthmentioning
confidence: 99%
See 2 more Smart Citations
“…Overexpression of VvSWEET10 in grapevine calli and tomatoes increased the glucose, fructose, and total sugar levels significantly ( Zhang et al, 2019 ). VvSWEET15 was highly expressed in three grape cultivars’ berries and obviously positively correlated with berry hexose content during ripening ( Ren et al, 2020 ). In summary, these findings demonstrated the role of VvSWEETs in sugar accumulation and biotic stress response.…”
Section: Molecular Biology Of Sink Strengthmentioning
confidence: 99%
“…Five SuSy genes (VvSS1-5) have been identified in the grape genome ( Zhu et al, 2017 ). VvSS3 was reported to co-express with VvSWEET15 to regulate sucrose hydrolysis and transport, leading to increase hexose accumulation in grapes ( Ren et al, 2020 ). Invertase hydrolyzes sucrose irreversibly into glucose and fructose and has a crucial function in establishing and maintaining sink metabolism, and hence considered to be a central molecular sink strength determinant ( Koch, 2004 ).…”
Section: Molecular Biology Of Sink Strengthmentioning
confidence: 99%
See 1 more Smart Citation
“…Five SuSy genes (VvSS1-5) have been identified in the grape genome (Zhu et al, 2017). VvSS3 was reported to co-express with VvSWEET15 to regulate sucrose hydrolysis and transport, leading to increase hexose accumulation in grapes (Ren et al, 2020). Invertase hydrolyzes sucrose irreversibly into glucose and fructose and has a crucial function in establishing and maintaining sink metabolism, and hence considered to be a central molecular sink strength determinant (Koch, 2004).…”
Section: Sugar Transporters and Sugar-cleaving Enzymes In Grapementioning
confidence: 99%
“…(Zhang et al, 2006;Xie et al, 2009). While some studies reported invertase and hexose transporters are unnecessary for sugar differential accumulation among cultivars (Ren et al, 2020), others found that it was mainly due to acid invertase activity (Guan, 2011). However, no functional identification is focused on the member of VvSSs or invertase family in grape so far.…”
Section: Sugar Transporters and Sugar-cleaving Enzymes In Grapementioning
confidence: 99%